Peramalan Harga Saham PT. Bank Central Asia, Tbk dengan Menggunakan Metode ARIMA - Gubu, La; Bakti Sadewa, Muhammad Alfian; Pimpi, La (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this research is to analyze the fluctuations and quantity of daily stock closing data of PT. Bank Central Asia Tbk (BCA) during the period from January 3, 2022, to December 30, 2022, and forecast the closing stock price in January 2023 using the ARIMA model. The research procedure was conducted step by step, including data collection, descriptive analysis, testing data stationarity, determining ARIMA model parameters, writing ARIMA equation models, conducting diagnostic tests on the best ARIMA model, and making predictions or forecasts. The analysis shows that the stock closing prices in 2022 fluctuated with an average range of Rp 7,214.29 - Rp 8,851.14 per share. The highest closing price occurred in November 2022, while the lowest occurred in July 2022. The forecast for the daily closing stock price of BCA from January 2 to January 31, 2023, using the ARIMA Model (1,1,0), ranges from Rp 8,550.00 to Rp 8,550.86. The MAPE value obtained from the forecasting result is 1.07%, indicating that the ARIMA model is highly effective in forecasting the closing stock price of BCA in January 2023. This research provides valuable insights into stock price fluctuations for stakeholders in the stock market. Keywords: fluctuations, ARIMA, stock closing prices, forecast.